ANALISIS KAJIAN KINERJA GURU BERDASARKAN KEDISIPLINAN, FASILITAS KERJA, BEBAN KERJA DAN LINGKUNGAN KERJA (Studi kasus: Guru SMK Negeri Se-Kabupaten Bireuen) - Win, Muntasir; Win (LPPM-UNIKI, 2022)
This study aims to examine teacher performance based on discipline, work facilities, workload and work environment. With a Case Study of a State Vocational School Teacher in Bireuen. The study was conducted on 171 State Vocational High School teachers with Productive Civil Servant status in Bireuen Regency, with a questionnaire instrument that had been tested for validity and reliability. Path analysis results show a). there is a significant influence of teacher discipline on the performance of teachers, contributing 6.50 percent. b). The factor of work facilities has a positive and significant impact on the performance of State Vocational School teachers in Bireuen Regency, which is quite large at 19.58 percent. c). The workload aspect also has an effect of 8.75 percent on teacher performance, d). The results of the data analysis also proved that the work environment of the State Vocational High School in Bireuen Regency had a significant effect on teacher performance, which was 11.54 percent. and e) Simultaneously the variables of discipline, work facilities, workload, work environment in schools, show an influence on the performance of State Vocational High School teachers in Bireuen Regency, amounting to 46.3 percent